2020
DOI: 10.3390/rs12152480
|View full text |Cite
|
Sign up to set email alerts
|

Species Monitoring Using Unmanned Aerial Vehicle to Reveal the Ecological Role of Plateau Pika in Maintaining Vegetation Diversity on the Northeastern Qinghai-Tibetan Plateau

Abstract: Plateau pika (Ochotona curzoniae, hereafter pika) is considered to exert a profound impact on vegetation species diversity of alpine grasslands. Great efforts have been made at mound or quadrat scales; nevertheless, there is still controversy about the effect of pika. It is vital to monitor vegetation species composition in natural heterogeneous ecosystems at a large scale to accurately evaluate the real role of pika. In this study, we performed field survey at 55 alpine grassland sites across the Shule River … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…The results of this study showed a density of 5500 pika burrows/ha in degraded alpine shrub meadow, whereas surveys conducted in the western part of the southern Qilian Mountains have shown that the average number of pika burrows in normal grassland is 300–800 burrows/ha (Qin, Sun, et al, 2020; Qin et al, 2019; Yi et al, 2016). In contrast, studies of degraded alpine grassland in the hinterland of QTP found the average number of pika burrows to be 2700–4775 burrows/ha (Liu et al, 2017; Tian et al, 2019; Wang et al, 2020; Wei et al, 2013), and in the degraded grasslands of the eastern QTP, the density of pika burrows can even reach 7066 burrows ha −1 (Zhang et al, 2021), which is close to our results.…”
Section: Discussionmentioning
confidence: 63%
“…The results of this study showed a density of 5500 pika burrows/ha in degraded alpine shrub meadow, whereas surveys conducted in the western part of the southern Qilian Mountains have shown that the average number of pika burrows in normal grassland is 300–800 burrows/ha (Qin, Sun, et al, 2020; Qin et al, 2019; Yi et al, 2016). In contrast, studies of degraded alpine grassland in the hinterland of QTP found the average number of pika burrows to be 2700–4775 burrows/ha (Liu et al, 2017; Tian et al, 2019; Wang et al, 2020; Wei et al, 2013), and in the degraded grasslands of the eastern QTP, the density of pika burrows can even reach 7066 burrows ha −1 (Zhang et al, 2021), which is close to our results.…”
Section: Discussionmentioning
confidence: 63%
“…To verify the suitability and feasibility of UAVs in cold regions, we organized a Special Issue entitled "Applications of UAVs in Cold Region Ecological and Environmental Studies". Eight papers were published in this issue [1][2][3][4][5][6][7][8]. Among them, 1, 2 and 5 papers focused on studies conducted in the Arctic, Antarctic and Qinghai-Tibetan Plateau, respectively.…”
mentioning
confidence: 99%
“…The common camera (with red, green and blue bands) was equipped with UAVs in all studies; only two studies used multispectral and thermal infrared cameras to retrieve surface temperature and soil moisture [7,8]. The flight height ranged from 2 m to observe grassland vegetation species [6] to 20-65 m to observe vegetation patches, surface type and animal [3,5,6], and 150-500 m to study the features of glacier [1,2]. Half studies used mosaic flight ways, which covered all areas of each study area, and the others used typical ecological sampling methods to take aerial photos at each point [4][5][6]8].…”
mentioning
confidence: 99%
See 2 more Smart Citations